The Effect of Scoliosis Orthosis on the Reduction of Cobb Angle in Scoliosis Patients: A Meta-Analysis - Suprayogi, Dody; Kristiyanto, Agus; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Scoliosis is a spinal deformity that often occurs in adolescents with a prevalence of 0.47% -5.2% worldwide. The prevalence of scoliosis in Asia was about 2.25% of the population. In Surabaya, Indonesia, 6.37% of students from 784 schools who conducted scoliosis screening tests positively had scoliosis. In addition, 9 out of 300 students in Surakarta positively had scoliosis. This study aimed to estimate the effect of using scoliosis orthosis in reducingcobb angle in scoliosis patients by conducting a meta-analysis on theseveral similar articles.Subjects and Method: This study used a meta-analysis by systematically reviewing the several similar articles from PubMed, ScienceDirect, and Google Scholar. The keywords were